Peredaran Narkotika Jenis Sabu Oleh Anak Dibawah Umur Dan Peran Keluarga Mencegah Anak Terjerumus Dalam Kejahatan Narkotika - Hilmi Alhalim; Abdul Jalil Salam (Program Studi Hukum Pidana Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study plans to (1) know and break down the elements that cause opiates flow by minors, and (2) know and dissect the significant job of the family to keep youngsters from falling into the universe of opiates. The sort of exploration utilized in this study is experimental legitimate examination. The area of the exploration was done at the Aceh Besar Territorial Police. Information assortment procedures utilizing record concentrate on methods, perception and meetings. Subjective information handling and examination procedures. That's what the outcomes showed (1) the type of chronic drug use committed by minors was brought about by different elements including natural variables, family congruity conditions and monetary elements. Likewise, (2) the significant job of guardians to keep youngsters from falling into the universe of medications is, should do great nurturing correspondence and control, guardians should have the option to adjust to the states of nurturing that should be lived because of changes in the job and weight of nurturing obligations, guardians play a significant part in directing and going with their kids both in proper training and non-formal schooling. Then, at that point, in the event that the youngster has perpetrated the wrongdoing, the activity is the right policing that the kid can change and acknowledge what they fouled up.